SISTEM PELAYANAN RESERVASI GEDUNG SERBAGUNA KOTA UNGARAN BERBASIS VB.NET - Dwi Prakoso, Vikko; Handayani UN, Dewi (Information Technology and Telematics, 2018)
Abstract -Leases made in the Ungaran City multipurpose building are still done by recording in the archive book, so that the reservation service process has not been effective, less accurate and prone to data loss. In this study the software development method used is the prototype method with the design of UML (Unified Modeling Language) designs such as usecase diagrams, class diagrams, activity diagrams, and sequence diagrams. Pada reservation service system made, computerized building rental process and using database storage to minimize data loss.